2013
DOI: 10.3899/jrheum.121507
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl Ester Transfer Protein in Patients with Rheumatoid Arthritis

Abstract: CETP is downregulated in patients with RA who are taking glucocorticoids. Low CETP activity is associated with an increased level of cardiovascular risk in patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
4
6
1
Order By: Relevance
“…Therefore, in active RA patients, besides inflammation, fat mass distribution can be contributing to elevated CETP activity. In contrast with our results, FerrazAmaro et al [50] have previously reported low CETP activity in RA patients under treatment with glucocorticoids. In parallel, the authors have also documented elevated HDL-C levels, an observation that differs from our results and from data earlier reported by others [5].…”
Section: Discussioncontrasting
confidence: 86%
“…Therefore, in active RA patients, besides inflammation, fat mass distribution can be contributing to elevated CETP activity. In contrast with our results, FerrazAmaro et al [50] have previously reported low CETP activity in RA patients under treatment with glucocorticoids. In parallel, the authors have also documented elevated HDL-C levels, an observation that differs from our results and from data earlier reported by others [5].…”
Section: Discussioncontrasting
confidence: 86%
“…In addition, the fact that SSc display lower levels of total cholesterol and higher triglycerides than controls has also been previously described [10,11], although in smaller cohorts that lacked multivariate analysis. The lipid pro le differences between patients and controls found in our study are in accordance with the 'lipid paradox' [15] described in other in ammatory diseases like RA [6,16,17] or SLE [18]. This means that untreated in ammatory diseases are associated with lower levels of total cholesterol and LDL-cholesterol, and it is believed that this may stem from the lipid-lowering effects of systemic in ammation.…”
Section: Discussionsupporting
confidence: 90%
“…Lipid profile differences between patients and controls found in our report are in accordance with the 'lipid paradox' (32) described in other inflammatory diseases such as rheumatoid arthritis (17,33,34) or systemic lupus erythematosus (35). This means that individuals with untreated inflammatory diseases or those with these conditions who have high disease activity exhibit lower levels of total cholesterol and LDL cholesterol, and it is believed that this may be due to the lipid-lowering effects of systemic inflammation.…”
Section: Discussionsupporting
confidence: 90%